Pengisian KRS Online Berbasis Layanan SMS Gateway Di Fakultas Teknik Universitas Riau - Anggie Kurnia Fareri; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The purpose of this research is to helping students of University of Riau adding major that they wanted during KRS schedule. This system was build and develop using MySQL database. The system has web-based for a website and sms-based for adding major students which message sent to sms gateway server, and will be process using trigger and distribute to tables that has been created. Next step, the system get the information from student’s message that will be process and will get reply message (autoreply) for noticing students their message have sent and processedThe result of this research is to give students the alternative way to adding major during KRS schedule, and that is using sms gateway technology while student can’t get access to the internet and can’t KRS done on schedule. And be an option University of RiauKeyword:Sms, Database, trigger, MySQL